Biometric analysis of Palmer mangoes - Martins Freitas, Rutinéia; Silva Peixoto, Lucas; Rodrigues de Oliveira, Hygor; Resende, Osvaldo; Rocha Plácido, Geovana; Fonseca Souza, Alex; Moresco, Karla Suzana; Romani, Viviane Patrícia (Comunicata Scientiae, 2024)
damages, resulting in a substantial waste of approximately 30% of the production. Among widely marketed varieties, the 'Palmer' cultivar stands out due to its flavor and coloration. The efficiency in the transportation and storage of these fruits is intricately linked to various attributes, especially their physical characteristics. In this context, the present study conducted a biometric evaluation of 145 'Palmer' mangoes harvested in Coxim, Mato Grosso do Sul. Parameters such as weight, length, width, and thickness of the fruits were analyzed using a semi-analytical balance and caliper. The results revealed that the mangoes produced in Coxim weigh around 396 g, with a length of 13 cm, width of 8 cm, and thickness of 7.5 cm. These measurements are smaller than the commercially marketed fruits of the same variety but larger than those of the Espada, Rosa, and Van Dyke varieties. Additionally, all analyzed variables showed a positive correlation, indicating that as one variable increases, the others also increase. This underscores the importance of special care in handling fruits throughout the supply chain, given their density of 0.534 g/cm³ and extensive contact area. These findings emphasize the pressing need for improvements in packaging, transportation, and storage processes to reduce losses and waste, thereby contributing to a more efficient and sustainable management in the mango supply chain.